In Vivo Time Domain Optical Imaging of Renal Ischemia-Reperfusion Injury: Discrimination Based on Fluorescence Lifetime - Abedelnasser Abulrob; Eric Brunette; Jacqueline Slinn; Ewa Baumann; Danica Stanimirovic (Molecular Imaging)
Fluorescence lifetime is an intrinsic parameter of the fluorescent probe, independent of the probe concentration but sensitive to changes in the surrounding microenvironment. Therefore, fluorescence lifetime imaging could potentially be applied to in vivo diagnostic assessment of changes in the tissue microenvironment caused by disease, such as ischemia. The aim of this study was to evaluate the utility of noninvasive fluorescence lifetime imaging in distinguishing between normal and ischemic kidney tissue in vivo. Mice were subjected to 60-minute unilateral kidney ischemia followed by 6-hour reperfusion. Animals were then injected with the near-infrared fluorescence probe Cy5.5 or saline and imaged using a time-domain small-animal optical imaging system. Both fluorescence intensity and lifetime were acquired. The fluorescence intensity of Cy5.5 was clearly reduced in the ischemic compared with the contralateral kidney, and the fluorescence lifetime of Cy5.5 was not detected in the ischemic kidney, suggesting reduced kidney clearance. Interestingly, the two-component lifetime analysis of endogenous fluorescence at 700 nm distinguished renal ischemia in vivo without the need for Cy5.5 injection for contrast enhancement. The average fluorescence lifetime of endogenous tissue fluorophores was a sensitive indicator of kidney ischemia ex vivo. The study suggests that fluorescence lifetime analysis of endogenous tissue fluorophores could be used to discriminate ischemic or necrotic tissues by noninvasive in vivo or ex vivo organ imaging.